The clinical characteristics and manifestations of cytomegalovirus esophagitis. Issue 4 (1st June 2016) - Wang, H.-W.; Kuo, C.-J.; Lin, W.-R.; Hsu, C.-M.; Ho, Y.-P.; Lin, C.-J.; Su, M.-Y.; Chiu, C.-T.; Wang, C.-L.; Chen, K.-H.
Summary: Esophagitis is the second most common gastrointestinal manifestation of cytomegalovirus (CMV) infection after colitis. CMV esophagitis has been reported in patients who have undergone transplantation, are on long-term renal dialysis, or who have the human immunodeficiency virus infection. This study aimed to investigate the clinical characteristics and manifestations of CMV esophagitis in patients who underwent diagnostic endoscopy. A total of 16 patients with histologically proven CMV infection were identified from 1539 patients with esophageal ulcers and analyzed retrospectively (January 2006 to December 2013). Patients' personal data (age, smoking, and alcohol consumption), underlying systemic diseases (diabetes mellitus, end-stage renal disease, and chronic obstructive pulmonary disease), malignancy, indication for esophagogastroduodenoscopy, endoscopic characteristics, and diagnostic methods (pathological or serological findings) were collected for further analysis. Among the patients with CMV esophagitis, the mean age was 59.94 years (range, 23–84 years). The male : female ratio was 1.67:1. Odynophagia and epigastralgia were common symptoms. Of the 16 patients, 3 (18.75%) were infected with the human immunodeficiency virus and 9 (56.25%) had an underlying malignancy, including lung cancer (6 patients), esophageal cancer (2 patients), gastric cancer (1 patient), ampulla of Vater cancer (1 patient), and lymphoma (1 patient). Six of the 9 patients (66.7%) with malignancy had been administered concurrent chemoradiotherapy (CCRT). In this study, patients with malignancy who had been administered CCRT were at increased risk for CMV esophagitis, which had not been reported before in the literature. CMV esophagitis should be considered as a potential treatment-related complication of CCRT.